Zakres wykorzystania pnia i jakość sortymentów pozyskanych harwesterem w drzewostanie sosnowym II klasy wieku - Mederski, Piotr; Bembenek, Mariusz; Brunka, Mariusz; Karaszewski, Zbigniew; Naparty, Kwiryn; Werk, Konrad (Leśne Prace Badawcze, 2019)
Obtaining high harvester efficiency in young pine stands during early thinning is a challenging management practice. One of the difficulties lies in achieving the optimal use of the tree trunk for assortments and obtaining satisfactory timber quality. The objective of this research was to find out 1) how much of the tree trunk can be processed by a harvester to produce logs, and 2) the quality of the assortments in terms of log length accuracy and delimbing quality. The work was carried out in a 31-year-old pine stand in Northern Poland with a Vimek 404 5T harvester using a Keto Forst Silver head for early thinning. Eighty sample plots were set up within the stand for detailed tree analysis after harvesting. The total length of the assortments from each tree was measured as well as the minimal top diameter (under bark). Additionally, the lengths of the bottom, middle and top logs were measured as well as the height of the knots after delimbing. On average, 70% of the total tree height was used for assortments and logs were processed up to a mean top diameter of 5.3 cm under bark. The length accuracy was very high: 81% of the logs had the expected length, more than 90% had a commercially acceptable length, while only 0.7% of the logs were too long. The average height of knots after delimbing was up to 1 cm. We therefore conclude that using a Vimek 404 5T in the 31-year-old pine stand was an effective solution for trunk processing and obtaining quality assortments.